ANALISIS BUDAYA, MOTIVASI DAN PERAN DOSEN TERHADAP MINAT BERWIRAUSAHA MAHASISWA MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PATTIMURA AMBON - Ferdy Leuhery (Manis: Jurnal Manajemen dan Bisnis, 2019)
This research was conducted on Student Department of Economics andBusiness Faculty of Pattimura University of Ambon. The purpose of this study isamong others to get a picture of student entrepreneurship interest. The formulationof the problem is how the culture and motivation directly influence the role oflecturers and how the culture and motivation directly affect the entrepreneurshipintent of the students majoring in the management of the Faculty of Economicsand Business Pattimura University Ambon. This research method is Survey withsimple random sampling technique with quantitative analysis approach. Datacollection using questionnaires. Data is processed using Lisrel. Analyzer usingMultivariate SEM (Structural Equation Model). The result shows that culture andmotivation influence to the role of lecturer, culture and motivation influence toentrepreneurship intention and lecturer role influence to student entrepreneurshipintention.